Diversity and assembly patterns of mangrove rhizosphere mycobiome along the Coast of Gazi Bay and Mida Creek in Kenya. - Edith M Muwawa; Huxley M Makonde; Chinedu C Obieze; Isabelle G de Oliveira; Joyce M Jefwa; James H P Kahindi; Damase P Khasa (PLoS ONE, 2024)
Fungi are among key actors in the biogeochemical processes occurring in mangrove ecosystems. In this study, we investigated the changes of fungal communities in selected mangrove species by exploring differences in diversity, structure and the degree of ecological rearrangement occurring within the rhizospheres of four mangrove species (Sonneratia alba, Rhizophora mucronata, Ceriops tagal and Avicennia marina) at Gazi Bay and Mida Creek in Kenya. Alpha diversity investigation revealed that there were no significant differences in species diversity between the same mangrove species in the different sites. Rather, significant differences were observed in fungal richness for some of the mangrove species. Chemical parameters of the mangrove sediment significantly correlated with fungal alpha diversity and inversely with richness. The fungal community structure was significantly differentiated by mangrove species, geographical location and chemical parameters. Taxonomic analysis revealed that 96% of the amplicon sequence variants belonged to the Phylum Ascomycota, followed by Basidiomycota (3%). Predictive FUNGuild and co-occurrence network analysis revealed that the fungal communities in Gazi Bay were metabolically more diverse compared to those of Mida Creek. Overall, our results demonstrate that anthropogenic activities influenced fungal richness, community assembly and their potential ecological functions in the mangrove ecosystems investigated.